2017
DOI: 10.1021/acs.macromol.7b00706
|View full text |Cite
|
Sign up to set email alerts
|

Topology-Dependent Chain Stiffness and Local Helical Structure of Cyclic Amylose Tris(3,5-dimethylphenylcarbamate) in Solution

Abstract: Conformational properties of rigid and semiflexible cyclic chains are still unclear owing to few experimental researches on dilute solution properties. Five cyclic amylose tris(3,5dimethylphenylcarbamate) (cADMPC) samples ranging in the weight-average degree of polymerization from 23 to 150 were prepared from enzymatically synthesized cyclic amylose. Light scattering and small-angle X-ray scattering measurements were made on the samples to determine the weight-average molar mass Mw, the particle scattering fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…While the shape at high q region of each sample is substantially similar to that for the corresponding linear chain, a significant peak is found at the low-q range only for the cyclic chain. Similar tendency was also found for other cyclic amylose carbamates [22][23][24]37].…”
Section: Dimensional and Hydrodynamic Properties In Solutionsupporting
confidence: 84%
See 4 more Smart Citations
“…While the shape at high q region of each sample is substantially similar to that for the corresponding linear chain, a significant peak is found at the low-q range only for the cyclic chain. Similar tendency was also found for other cyclic amylose carbamates [22][23][24]37].…”
Section: Dimensional and Hydrodynamic Properties In Solutionsupporting
confidence: 84%
“…While P(q) of the wormlike ring cannot be calculated analytically, Tsubouchi et al [64] developed a Monte Carlo simulation method to calculate the particle scattering function Pc(q) of thin wormlike ring. Furthermore, if the chain thickness is taken into account by the touched-bead model as follows, ( ) (9) we reported that the resultant P(q) successfully reproduced the experimental data for the three amylose derivatives, that is, cATPC, cATBC, and cADMPC [24,44]. A curve fitting procedure was examined assuming log-normal molar-mass distribution with Ð = 1.05 and 1.20.…”
Section: Analyses In Terms Of the Cyclic Wormlike Chain: Catodcmentioning
confidence: 94%
See 3 more Smart Citations